Smoking behavior and hypertension among health workers during the COVID-19 pandemic: a case study in Java and Bali-Indonesia - Misnaniarti,; Nugraheni, Wahyu Pudji; Nantabah, Zainul Khaqiqi; Restuningtyas, Fraschiska Rizky; Hartono, Risky Kusuma; Rachmawati, Tety; Mubasyiroh, Rofingatul; Kusnali, Asep (Frontiers in Cardiovascular Medicine, 2023)
Background Health workers who should be role models for the community not to smoke and live a healthy life are still consuming cigarettes. Java and Bali (especially Java) are the biggest contributors to health worker deaths due to COVID-19 in Indonesia. This study aims to determine the association of smoking behavior and hypertension among health workers in Java and Bali. The researchers conducted this study in 2021 and designed it with a cross-sectional design. Data was collected online using the Lime Survey as a data collection tool. The data analysis used was logistic regression to determine the association of smoking and hypertension. Result A number of 7.6% of health workers were still smoking and 10.4% were suffering from hypertension during the COVID-19 pandemic. This study shows that the proportion of health workers with hypertension is two times that of smokers (18.0%) compared to non-smokers (9.8%). Logistic regression showed that smoking has a 20% higher risk of developing hypertension (OR = 1.97; 95%CI = 1.01–1.41; p = 0.034). Conclusion Among health workers on the islands of Java and Bali, there are still many who smoke, and this puts them at a higher risk of experiencing hypertension.